Biodiversidad marina de Costa Rica: Filo Porifera - Cortés, Jorge (Universidad de Costa Rica, 1996)
This, the first paper on a series on the current knowledge of the marine biodiversity of Costa Rica, covers the Phylum Porifera, the sponges. Based on the literature and other sources of inforrnation, a total of 38 species in 27 genera, 20 families, 9 orders and two subcIasses of the Class Demospongea are reported for Costa Rica, together with their distribution and source of inforrnation. All are from the Caribbean coast. There are no published repbrts on sponges from the Pacific of Costa Rica